Indium-assisted aluminium-based stereoselective allylation of prostereogenic α,α-disubstituted cycloalkanones and imines - Reddy, C.; Babu, S.A.; Aslam, N.A. (Royal Society of Chemistry, 2014)
The use of a catalytic amount of InCl3 in combination with Al0 for the allylation of a variety of prostereogenic α,α-disubstituted (hindered) cycloalkanones, 1,2-dione-based systems and various imino systems (C[double bond, length as m-dash]N functional groups) is reported. The stereoselective InCl3-catalyzed Al-based allylation of various 2-substituted-2-carbethoxycycloalkanones gave the corresponding products with moderate to excellent diastereoselectivity. The allylation and propargylation of imines including α-imino esters using a catalytic amount of InCl3 in combination with Al0 gave the corresponding allylated and propargylated compounds in moderate to good yields. If γ-substituted allylic halides were added to imino compounds, low to very good diastereoselectivity was obtained. The allylation of chiral N-tert-butylsulfinyl imine systems gave the corresponding products in moderate yields with good to excellent diastereoselectivity.
Keywords: Cycloalkanones; Stereo-selective; Prostereogenic